2006
DOI: 10.2353/ajpath.2006.060086
|View full text |Cite
|
Sign up to set email alerts
|

E- and P-Selectins Synergistically Inhibit Bleomycin-Induced Pulmonary Fibrosis

Abstract: The development of bleomycin-induced lung injury, which is a model of pulmonary fibrosis, results from inflammatory cell infiltration, a process highly regulated by the expression of multiple adhesion molecules. Therefore, bleomycin-induced lung fibrosis was examined in E-selectin ؊/؊ mice, P-selectin ؊/؊ mice, and E-selectin ؊/؊ mice treated with anti-P-selectin monoclonal antibody (mAb) in comparison of wild-type mice. E-selectin ؊/؊ mice treated with anti-P-selectin mAb exhibited augmented lung fibrosis his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The roles of P-selectin in the pathogenesis of SSc remain unclear. In lung fibrosis mouse model induced by intratracheal bleomycin administration, P-selectin deficiency did not significantly affect the fibrosis of lungs [48]. On the other hand, another study showed that the loss of P-selectin augmented the fibrosis of both skin and lungs induced by intracutaneous bleomycin injection [30].…”
Section: Discussionmentioning
confidence: 95%
“…The roles of P-selectin in the pathogenesis of SSc remain unclear. In lung fibrosis mouse model induced by intratracheal bleomycin administration, P-selectin deficiency did not significantly affect the fibrosis of lungs [48]. On the other hand, another study showed that the loss of P-selectin augmented the fibrosis of both skin and lungs induced by intracutaneous bleomycin injection [30].…”
Section: Discussionmentioning
confidence: 95%
“…This may result in differential production of cytokines, which may then directly or indirectly influence the development of dermal sclerosis, pulmonary fibrosis, and inflammatory cell infiltration. Previous studies have demonstrated that loss of L-selectin and/or ICAM-1 function inhibits lung fibrosis induced by intratracheal bleomycin treatment (14), while loss of P-selectin and/or E-selectin function augments it (23). These studies suggest that the mechanisms, by which cell adhesion molecules regulate tissue fibrosis, could be through the regulation of Th1 and Th2 cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…BAL cells were prepared as described elsewhere (23). Briefly, bleomycin- or PBS-treated mice were sacrificed and both lungs were excised.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…L-selectin deficiency inhibited lung fibrosis, but P-selectin deficiency and E-selectin deficiency augmented the fibrosis [29]. Another study involving E-selectin −/−, P-selectin −/− mice also revealed an inhibitory role of E-selectins in the development of bleomycin-induced pulmonary fibrosis [36]. Both studies conducted flow cytometric analysis between cell adhesion molecule-deficient mice treated with bleomycin and WT mice and found that loss of cell adhesion molecule function selectively altered the trafficking pattern of fibrogenic Th2 and Th17 cells and anti-fibrogenic Th1 cells to the lung.…”
Section: Discussionmentioning
confidence: 97%